Characterisation of signal-induced noise in Hamamatsu R11265 Multianode Photomultiplier Tubes. (23rd November 2021) - Andreotti, M.; Capelli, S.; Cavallero, G.; Chiozzi, S.; Cotta Ramusino, A.; D'Ambrosio, C.; Fiorini, M.; Franzoso, E.; Frei, C.; Gallorini, S.; Gambetta, S.; Giugliano, C.; et al.
Abstract: Signal-induced noise is observed in Hamamatsu R11265 Multianode Photomultiplier Tubes, manifesting up to several microseconds after the single photoelectron response signal and localised in specific anodes. The mean number of noise pulses varies between devices, and shows significant dependence on the applied high-voltage. The characterisation of this noise and the mitigation strategies to perform optimal single-photon counting at 40 MHz, as required by the LHCb Ring-Imaging Cherenkov detectors, are reported.